Australijskie reakcje na wydarzenia 1956 roku w Polsce - Rudziński, Adrian; Korobacz, Victor (Pamięć i Sprawiedliwość, 2016)
This article examines reaction in Australia and Australian foreign policy responses to Poland’s June 1956 crisis - Poznanski Czerwiec. Poznan’s June events prompted immediate Australia-wide demonstrations and protests by Polish emigres who were supported by friends and allies in the Catholic Church and the anti-communist movement. Nation-wide and well-attended demonstrations in Australia and subsequent approaches by Poles and supporters required a disinterested government to develop a position on Poznan. Pressure on the government for a response, potentially disruptive to its foreign policies, was applied only by elements within the Australian political scene that posed little threat to its future. Poznan’s greatest impact takes place within the peculiar nature of Australian politics where the Poznan issue was used to fan the flames of bitter rivalry within the labour movement by a strident anti-communist faction seeking to displace the Australian Labor Party and establish itself instead, as the legitimate representative of Australian workers. In taking up the Polish émigré cause, the Australian anti-communist leadership claimed the moral high-ground, but lacked sufficient strategic commitment to use their considerable parliamentary advantage to pressure the government to adopt a more muscular position on Poznan.